Design of Porous Carbon Adsorbents from Ethylene Glycol for Selective CO2 Adsorption - Zaman, Ali Can; Ustundag, Cem Bulent (WILEY-V C H VERLAG GMBH, 2024)
The production of affordable advanced porous materials is necessary for applications involving the capture of CO2. This study aimed to investigate the use of inexpensive liquid precursors in the production of CO2 sorbents. Porous precursors were produced through solvothermal processing of ethylene glycol via dehydration using sulfuric acid. Various pyrolysis and activation techniques were utilized on a carbon precursor to examine how different heat treatment methods affect surface chemical properties and the behavior of static CO2 adsorption at temperatures of 273 K, 298 K, and 313 K. Out of the studied carbons, the urea-treated pyrolyzed sample exhibited a CO2 uptake capacity of 0.93 mmol g(-1) at a pressure of 0.15 bar and a temperature of 298 K. This carbon exhibited a remarkable CO2/N-2 selectivity of 46, mainly due to its microporosity and a nitrogen content of 8.3 atomic percent. Moreover, the investigation of adsorption and chemical properties unveiled that nonoxidized sulfur exhibits favorable effects on CO2 adsorption, particularly at the temperature of 298 K. This study provides evidence that liquid precursors can be effectively employed to generate porous doped functional carbons or precursors using solvothermal conditions.
Keywords: microporous carbon; molecular precursor; surface chemistry; CO2 adsorption; doped carbon; NITROGEN-DOPED CARBON; PROTIC IONIC LIQUIDS; ONE-POT SYNTHESIS; ACTIVATED CARBON; HYDROTHERMAL SYNTHESIS; MICROPOROUS CARBONS; NANOPOROUS CARBONS; GRAPHENE OXIDE; CAPTURE; OXYGEN; Chemistry